Female at The Top Tier and Discretionary Accruals; Does Life Cycle Matter? - Fahrani, Meita; Arifin, Taufiq (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
This study seeks to furnish empirical evidence that the inclusion of females on the board of commissioners and directors affects discretionary accrual, and that the firm's life cycle moderates this influence. The sample technique employs purposive sampling. The sample comprised all non-financial companies listed on the Indonesia Stock Exchange from 2016 to 2021, resulting in a total of 2,694 observations. The analytical approach employs panel data regression analysis. The research findings demonstrate that female representation on the board of directors positively and significantly impacts discretionary accrual; conversely, female presence on the board of commissioners negatively affects discretionary accrual, while the firm life cycle moderating variable independently influences discretionary accrual. The firm's life cycle can influence the impact of female representation on the board of commissioners and the board of directors on accruals.Keywords: discretionary accruals, female, boards of commissioners, directors, firm life cycle.